Measurement and Expression of Exact Intraocular Pressure of Patient?s Eye(S) and to Determine Normal or Pathological IOP - Zubeda Irshad, Abid Nawaz, Bakht Samar Khan, Mustafa Iqbal (Pakistan Journal of Ophthalmology, 2010)
Purpose: To determine the exact and uniform IOP of patients eye(s) and need to redefine normal and pathological IOP leading to glaucoma. Material and Methods: A prospective descriptive study of 10000 eyes of 5000 patients out of Which 450 eyes were selected .The patients were examined in the department of Ophthalmology of Khyber teaching hospital Peshawar Pakistan from June 2003 to May 2008. All patients underwent IOP measurement with different tonometers that is Goldman, Perkins and Air puff at the same time. The IOP was measured with distant looking eye position and near looking eye position to ascertain the difference in IOP. Results: The distant looking IOP was higher as compared to near looking. Thus three Readings were obtained as distant looking IOP, near looking IOP and mean IOP. Conclusion: The present way of expressing IOP as single reading (e.g.20 mm Hg) need to be replaced by two readings i.e. distant looking/ near looking (DL/NL) e.g. 21/16 mm Hg or as mean of distant looking and near looking IOP (e.g. 18.5 mm Hg).